2011
DOI: 10.1016/j.jhep.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to terlipressin plus albumin in hepatorenal syndrome (HRS) type 1: Relationship of serum creatinine to hemodynamics

Abstract: Background & Aims Administration of terlipressin plus albumin is effective in reversing type 1 HRS as compared to albumin alone. However, only about 1/3 of patients respond to treatment, therefore, predictors of response and survival would help identify the patients most likely to benefit from treatment. Methods We analyzed our controlled trial of terlipressin vs. placebo (Gastroenterology 2008;134:1360) to define factors predictive of a response and to correlate hemodynamic changes to changes in renal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
161
2
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 19 publications
16
161
2
9
Order By: Relevance
“…Our observations regarding factors predictive of HRS reversal and survival essentially confirm what has been observed in previous studies,22, 23, 24, 25, 26, 27 with the exception of the absence of a precipitating cause for HRS‐1, absence of prior rifaximin use in the terlipressin group, and male sex in the placebo group – all new observations. The absence of prior rifaximin use as a factor predictive of HRS reversal in the terlipressin group is of interest; it is possible that patients without prior rifaximin exposure are less ill than those receiving rifaximin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our observations regarding factors predictive of HRS reversal and survival essentially confirm what has been observed in previous studies,22, 23, 24, 25, 26, 27 with the exception of the absence of a precipitating cause for HRS‐1, absence of prior rifaximin use in the terlipressin group, and male sex in the placebo group – all new observations. The absence of prior rifaximin use as a factor predictive of HRS reversal in the terlipressin group is of interest; it is possible that patients without prior rifaximin exposure are less ill than those receiving rifaximin.…”
Section: Discussionsupporting
confidence: 89%
“…For the placebo group, only the absence of alcoholic hepatitis and male sex were predictive of both longer transplant‐free survival and longer overall survival. While absence of alcoholic hepatitis is a known predictive factor for better survival,22 the finding of male sex as a predictor should be examined further. Overall survival at day 90 was significantly lower in females than in males; however, females receiving terlipressin showed a trend towards improved survival compared with those receiving placebo, and the survival estimate was similar to that for males.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, approximately one-third of HRS type 1 patients in 2 large controlled clinical trials responded to terlipressin. 43 Although overall survival was not changed, improved renal function before transplant makes peritransplant and posttransplant management easier, 44 and improved renal function before transplant improves posttransplant renal function and decreases mortality. 45 Dialysis is used in patients with HRS but usually as a bridge to LT.…”
Section: Renal Failurementioning
confidence: 99%
“…This leads to ignore patients with less increased SCr though they are already presenting HRS and could receive early treatment and benefit from improved outcomes. In 2011, a study by Boyer et al [26] found that in cirrhotic patients with HRS, initial SCr was an independent predictor of the probability to get a response to terlipressin, and also to survive at 3 mo. In this study, every 1 mg/dL of increase of SCr was associated with an increase of 50% of the risk of death.…”
Section: Hrsmentioning
confidence: 99%